Business Moral Values of Supervisors and Subordinates and Their Effect on Employee Effectiveness - Jiang, Ding-Yu; Lin, Yi-Chen; Lin, Lin-Chin (2011)
Business moral values are defined as the personal moral values held by individuals who are engaged in business interactions. Direct supervisors may play an important role in shaping the business moral values of their subordinates. Using 264 supervisor–subordinate dyadic data from Taiwanese organizations, the study investigated the relationships among supervisor business moral values, subordinate business moral values, subordinate organizational commitment, job performance, and attendance. The results indicated that supervisor business moral values were positively associated with subordinate business moral values, and that the latter mediated the relationship between the former and subordinate outcomes. Implications for business moral values research are discussed.
Keywords: supervisor–subordinate dyads; Organizational Commitment; Job performance; business moral values; Attendance